The potency of combination of tomato juice and sweet orange on blood pressure in pre-hypertensive people - Dwi Preci Anugrah; Tonny Cortis Maigoda; Risda Yulianti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Hypertension, if left untreated, causes complications in important organs such as the heart, eyes, kidneys, and brain. Tomatoes and sweet oranges have benefits in lowering blood pressure, but these two food ingredients have not been combined to be used as food ingredients in lowering blood pressure. The purpose of this study was to determine the effect of a combination of tomato and sweet orange juice on blood pressure in employees at the office of the PT Agri Andalas Seluma Regency. The research design was a pre-experiment with pre-and post-test designs. The subjects were employees at PT Agri Andalas, totaling 15 people, conducted by purposive sampling. The treatment was given a combination of juice in the form of 150 g of tomatoes and sweet orange juice as much as 50 ml then given, and water was added as much as 50 ml so as to produce a combination of tomato and sweet orange juice as much as 250 ml. The intervention was performed for 7 days. Results: The systolic blood pressure from136,1 mmHg decreased from 131,4 mmHg. Likewise in diastolic blood pressure, there was a change from 86,3 mmHg to 81,8 mmHg. There was a difference in systolic (p= 0,001) and diastolic (p= 0,001) blood pressure before and after treatment with a combination of tomato and sweet orange juice. In conclusion, the combination of tomatoes and sweet orange juice lowered blood pressure. The juice combination can be used as a functional food as an alternative for lowering blood pressure.